Genetic polymorphisms altering microRNA activity in psoriasis – a key to solve the puzzle of missing heritability?. Issue 9 (September 2014) - Pivarcsi, Andor; Ståhle, Mona; Sonkoly, Enikő
Abstract Psoriasis is a chronic immune‐mediated skin disease in which the balance in the interplay of immune cells and keratinocytes is disturbed. MicroRNAs (miRNAs) are endogenous small regulatory RNAs that stabilize cellular phenotypes and fine‐tune signal transduction feedback loops through the regulation of gene networks. Through the regulation of their multiple target genes, miRNAs regulate the development of inflammatory cell subsets and have a significant impact on the magnitude of inflammatory responses. Since the discovery of deregulated miRNA expression in psoriasis, we have learned that they can regulate differentiation, proliferation and cytokine response of keratinocytes, activation and survival of T cells and the crosstalk between immunocytes and keratinocytes through the regulation of chemokine production. In recent years, it became apparent that genetic polymorphisms in miRNA genes and/or in miRNA binding sites of target genes can affect miRNA activity and contribute to disease susceptibility. Psoriasis has a strong genetic background; however, the contribution of genetic variants involving miRNAs is largely unexplored in psoriasis. We propose that changes in miRNA‐mediated gene regulation may be a major contributor to the disturbed balance in immune regulation that results in chronic skin inflammation. In this viewpoint essay, we focus on the emerging new aspects of the role of miRNAs in psoriasis and propose that genetic polymorphisms that affect miRNA activity might be important in the pathogenesis of psoriasis.